Study of Some Sociodemographic Factors in Teenage Pregnancy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: Teen age pregnancy is associated with adverse labour outcome. Analysis of teenage pregnancy shown it was related to a range of social back ground, family and individual factors. Objective: To study the socio demographic factors related to teenage pregnancy and its complications. Methods: A cross sectional observational study was performed over a period of one year (September 2009- August 2010) at the obstetrics department of Chittagong Medical College Hospital. Consecutive six hundred pregnant mothers admitted for delivery that were fulfilled inclusion criteria included in study group. Among them 300 were teen aged (13- 19yrs) belongs to group A and 300 were adult (20-29 yrs) belongs to group B. Socio demographic factors like habitation, religion, family income, education, occupation, contraceptive use, pregnancy plan and antenatal care enquired. Labour complications i.e. prolong or obstructed, fetal distress, mode of delivery, stillbirth, birth weight and birth asphyxia was recorded on a preformed questionnaire and statistical analysis done by using SPSS package for windows version 12. Results: Teenage mother has significant lower mean age at delivery than adults (18.61-+72 vs. 23.87-+ 2.8yrs. P